A Literature review on the Identification of Variables for Measuring Hospital Efficiency in the Data Envelopment Analysis (DEA) - Fazria, Nokky Farra; Dhamanti, Inge (Unnes Journal of Public Health, 2021)
The selection of input and output variables usually pose a problem when carrying out efficiency assessment in hospitals. Data Envelopment Analysis (DEA) is an instrument that is used to calculate the efficiency of a hospital using some inputs and outputs. Therefore, this study aims to identify the most frequently used hospital inputs and outputs from an existing paper,, in order to assist the hospital management staffs in choosing the relevant variables that can represent available inputs, are easily accessible, and need improvement. It was conducted using keywords such as Ã¢â‚¬Å“hospital efficiencyÃ¢â‚¬Â and Ã¢â‚¬Å“DEA for hospitalÃ¢â‚¬Â to search for peer-reviewed journals in the PubMed and Open Knowledge Maps from the year 2014-2020. From, the 586 articles, 54 samples were obtained from the about 5-3504 hospitals which were analyzed from 23 countries. The results showed that, the five most used inputs were the number of beds, medical personnel, non-medical staff, medical technician staff and operational costs, while the most used outputs were number of inpatients, surgeries, emergency visits, outpatient service, and days of inpatients. These variables are often used for accessing the efficiency of hospitals in the DEA application.